Studying the empirical implications of the liberalization of airport markets. Issue 3 (September 2020) - Button, Kenneth
This paper offers an overview of what we know about the impacts of the economic regulation of commercial airports. It offers no new empirical findings, but rather considers the challenges of conducting ex post analysis of regulatory reform. It provides an overview of what completed studies have found and assesses whether regulations have achieved their objectives. Little is said about the desirability of these objectives. The focus is on the infrastructure needed to provide commercial passenger air services. Part of the discussion concerns the extent to which the results found in more recent studies offer replication of earlier findings. One function of applied analysis is to offer confirmation or refutation of the findings of prior studies, but this is often given short shrift compared to "novelty." The paper focuses, in particular, on matters concerning ownership, slot allocation, and supplementary incomes.